Research Review on the Damage Theoretical Model of Metal Materials - Qinhong FAN; Hongwei GAO; Zhibing CHU (Taiyuan Ligong Daxue xuebao, 2023)
The plastic deformation of metal material is accompanied by surface defects, internal defects, damage cracks, etc., and these defects seriously restrict the processing of metal and its performance improvement. Therefore, the continuous damage mechanics theory and the fine view of the damage mechanics theory were reviewed, and then according to the damage model construction, to effectively predict the material crack damage, thus making a good foundation for the subsequent secondary development and simulation application. By comparison, the Johnson-Cook model has been widely used by researchers in its simple multiplication form, owing to its excellent ability to predict strain rate and mechanical behavior in the temperature range. The model is very suitable for finite element program simulation and its verification, and has been continuously improved and optimized.